1984
DOI: 10.1159/000233458
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating Effect of Mercuric Chloride and Nickel Sulfate on DNA Synthesis of Thymocytes and Peripheral Blood Lymphocytes in Children

Abstract: Mercuric chloride and, to a lower extent, nickel sulfate, stimulated DNA synthesis of both thymocytes and peripheral blood lymphocytes. The metal allergens stimulated both celltypes at a lower degree than lectinic mitogens (PHA, Con A and PWM) did. In peripheral blood lymphocytes the stimulation degree was higher than in thymocytes after addition of metal allergens as well as lectinic mitogens. The presence of serum seemed to have a protective and potentiating role regarding the effect of mercuric chloride and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 7 publications
1
28
1
Order By: Relevance
“…One important factor in mercury-induced reactivity is the serum concentration used for culture. It has been reported that serum has a cellprotective role to the compound [17]. Monocytes have been shown to be more vulnerable to the toxic effect of HgCl 2 than T and B lymphocytes [18,21] and the toxic events have been proposed to be associated with programmed cell death [22].…”
Section: Dependence Of Adherent Cells For Hgcl 2 -Induced Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…One important factor in mercury-induced reactivity is the serum concentration used for culture. It has been reported that serum has a cellprotective role to the compound [17]. Monocytes have been shown to be more vulnerable to the toxic effect of HgCl 2 than T and B lymphocytes [18,21] and the toxic events have been proposed to be associated with programmed cell death [22].…”
Section: Dependence Of Adherent Cells For Hgcl 2 -Induced Reactivitymentioning
confidence: 99%
“…It is shown that both CD4 þ T cells and adherent cells are required for activation [14]. The mitogenic property of HgCl 2 has also been demonstrated on human lymphocytes in vitro [15][16][17]. In addition, mercury may interfere with mitogen (phytohaemagglutinin (PHA) and pokeweed mitogen (PWM))-induced lymphocyte reactivity, since the proliferation response is reduced in HgCl 2 -pretreated cultures [18].…”
Section: Introductionmentioning
confidence: 99%
“…Mercuric chloride is known as a polyclonal activa tor of T lymphocytes [1,2], and nickel sulfate acti vates T lymphocytes from nickel-allergic patients [3]. The stimulation, as regards mercuric chloride, might be mediated through a direct action on the lympho cytes via nuclear uptake [4], As regards nickel sulfate, the stimulation might partly be mediated by a direct action via nuclear uptake [5] and partly via participa tion of macrophages [3].…”
Section: Introductionmentioning
confidence: 99%
“…Mercuric chloride and nickel sulfate were obtained from Merck and were dissolved in 0.9% saline and used in the cultures at final concentrations of 5.5 x 10"6 and 3.8 x 10"' M, respectively, which have previously been found to be optimal for a mitogenic effect [9][10][11]. Unfractionated heparin (Heparin KabiVitrum, Stockholm, Sweden) and a low molecular weight heparin fragment (Fragmin KabiVitrum) were a gift from KabiVitrum.…”
Section: Test Substancesmentioning
confidence: 99%
“…Mercuric chloride is known as a polyclonal activa tor of human T lymphocytes [9,10,17], while nickel sulfate stimulates T lymphocytes from nickel-allergic subjects [11]. The stimulation, as regards mercuric chloride, probably is mediated through a direct effect on the cells via uptake in the nuclei [ 13] and as regards nickel sulfate might partly be mediated by a direct ac tion on lymphocytes via nuclear uptake and partly via participation of macrophages [11,12].…”
Section: Introductionmentioning
confidence: 99%